Mengenal Leuser dengan Arsitektur: Perancangan Museum Gunung Leuser dengan Pendekatan Arsitektur Organik - Ulwan, T.M. Inayatul; Ridwan, Nasrullah; Huda, Khairul (Jurnal RAUT, 2025)
Gunung Leuser National Park (TNGL) is a conservation area with exceptionally high biodiversity and serves as a habitat for endangered species such as tigers, orangutans, elephants, and Sumatran rhinos. Despite its significant ecological value, the area continues to face serious threats, including deforestation, illegal encroachment, poaching, and the impacts of climate changefurther exacerbated by the low level of public awareness regarding environmental conservation. In response to these challenges, the Mount Leuser Museum is designed as a public educational facility that serves as an entry point for understanding Leusers biodiversity and the urgency of its conservation. An organic architectural approach is applied in the design to establish harmony between the building and the natural environment. Through interactive spatial planning and integration with the sites landscape, the museum is intended to become an effective learning medium to increase public knowledge and strengthen community commitment toward the sustainable preservation of the Leuser ecosystem.